Balance de líneas en procesos productivos - Chimborazo Rocha, Galo Fernando (2017)
Today, companies face great challenges to provide quality services and products to customers and every day the competition absorbs the market by leaps and bounds, which involves raising techniques of improve ment that allow them to grow contributing to organizational development. Its main objective is to investigate the benefits that the Line Balance will produce in the production processes of the company La Picantina, which allowed to investigate scientific information according to the selected topic, validating its application through established theories of authors that support this philosophy, defining The methodology of balance of production lines and its feasibility of application in the company developing a proposal of evaluation in the productive processes. Thus the balance of lines is an important tool to improve production processes and optimization of resources, the company La Picantina showed the following problem: the lack of control tools in the production of products (sausages and sauces), Causes a low level of productivity and generates losses in the productive processes, so the following proposal was proposed for the balance of lines as an alternative to improve this problem. In order to carry out the project we used research methods such as the scientist, which allowed us to carry out the problem, and applied the qualitative and quantitative approaches, being fundamental in the development of the research, obtaining descriptive and statistical data of the The same information was obtained from different sources of bibliographical, documentary, field and statistical data, supporting the research to be carried out.